2021
DOI: 10.3389/fimmu.2021.687715
|View full text |Cite
|
Sign up to set email alerts
|

Humanized Mouse Model as a Novel Approach in the Assessment of Human Allogeneic Responses in Organ Transplantation

Abstract: The outcome of organ transplantation is largely dictated by selection of a well-matched donor, which results in less chance of graft rejection. An allogeneic immune response is the main immunological barrier for successful organ transplantation. Donor and recipient human leukocyte antigen (HLA) mismatching diminishes outcomes after solid organ transplantation. The current evaluation of HLA incompatibility does not provide information on the immunogenicity of individual HLA mismatches and impact of non-HLA-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…It was found that an innate immune mechanism emerged in the AR and proinflammatory cytokines activated by innate immune-stimulated T cell expansion during this pathway process [ 22 ]. Meanwhile, Ashwin et al observed that AR was an unregulated pathway in the immune response, and Subhayan et al detected that this pathway was related to the B cell receptor signaling pathway [ 23 , 24 ]. The association between AR and gliomas has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that an innate immune mechanism emerged in the AR and proinflammatory cytokines activated by innate immune-stimulated T cell expansion during this pathway process [ 22 ]. Meanwhile, Ashwin et al observed that AR was an unregulated pathway in the immune response, and Subhayan et al detected that this pathway was related to the B cell receptor signaling pathway [ 23 , 24 ]. The association between AR and gliomas has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…One of these approaches is to create humanized mouse models. These models are engrafted with human cells and tissues that impart human characteristics to mice and make the model a valuable tool for clinical translation [ 7 ]. The humanized mouse models mimic the human immune system; therefore, these models are mainly used to create patient-derived xenograft (PDX) models for cancer studies.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, controlling the H 2 O 2 concentrations upon systematic injection of n(LOx) will be an essential issue, which may be addressed by coadministrating CAT ( 40 ). We also note that the currently available humanized models have the limitation of human leukocyte antigen mismatch between the tumor and the human immune cells, which may induce treatment-independent immune response to tumor cells ( 41 ). Therefore, the evaluation and conclusions of therapeutic efficacy in humanized mice with tumor xenograft need to be carefully interpreted and supported by results in immunocompetent mice.…”
Section: Discussionmentioning
confidence: 99%